Rasionalisme Rene Descrates sebagai Pemicu Awal Kesuksesan dalam Berlogika Perspektif Pendidikan Abad 21 - Fatiha Nuria Ammarin; Hidayatul Maulidiyah; Kuswatun Khasanah; Moh. Faizin (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2024)
René Descartes' rationalism has an important role in forming the foundations of modern logic, which is the basis for success in critical and analytical thinking in the 21st century. Descartes, through the method of systematic doubt and cogito ergo sum, emphasized the importance of rational thinking and logical reasoning as the main tools in acquiring knowledge. In the context of 21st century education, Descartes' principles are applied in a curriculum that encourages students to think critically, evaluate arguments logically, and solve complex problems through an analytical approach. By adopting Descartes' approach, modern education focuses not only on the transfer of knowledge, but also on the development of deep and structured thinking skills, which are essential to face global challenges and continuously developing technology. Descartes' rationalism, therefore, provides a strong foundation for the success of logic and critical thinking in the contemporary era.